TEATRIKALISME DALAM PEMENTASAN “PEMBERDAYAAN KESEJAHTERAAN KELUARGA” - Eko Santosa (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2022)
The purpose of this study is to reveal theatricalism in the staging of "Family Welfare Empowerment"produced by Teater Amarta Yogyakarta on October 23, 2022 in the Concert Hall Taman BudayaYogyakarta. The current study is based on the concept of theatricalism as an opponent of realism in theculture of Western modern theater with the characteristics formulated by McTigue and Cohen. The aspectsanalysed include play, staging, and acting. The results of the study demonstrate that the play has thepotentials of theatricalism in a series of events that are consciously constructed to direct the attention ofthe audience to the event of performances through directional texts and scenes, opportunities forimprovisation, as well as the use of language and terms in dialogue. The staging contains theatricalismcharacteristics in which the stage arrangement is presented in the style of symbolism and is supported bythe arrangement of theatrical scenes which sometimes invites the audience to become part of theperformance. The acting side shows that the actors do not only play the role as a character but also ashimself through the improvisation. Hence, it shows that the play, staging, and acting achieve thecharacteristics of theatricalism which is, at the same time, contrary to realism Tujuan kajian ini adalah menyingkap teatrikalisme dalam pementasan “Pemberdayaan KesejahteraanKeluarga” produksi Teater Amarta Yogyakarta pada tanggal 23 Oktober 2022 di Concert Hall TamanBudaya Yogyakarta. Kajian ini berpijak pada konsep teatrikalisme sebagai penentang realisme dalam kulturteater modern Barat dengan ciri-ciri rumusan McTigue dan Cohen. Aspek yang dikaji adalah lakon,pemanggungan, dan akting. Hasil kajian memperlihatkan bahwa lakon memiliki potensi teatrikalismedalam rangkaian peristiwa yang dikonstruksi secara sadar untuk mengarahkan perhatian penonton padaperistiwa pementasan melalui keterangan laku dan adegan, peluang improvisasi, serta penggunaan bahasadan istilah dalam dialog. Pemanggungan memuat ciri teatrikalisme di mana tata panggung disajikan dengangaya simbolisme dan didukung oleh penataan adegan teatrikal yang terkadang mengajak penonton menjadibagian dari pertunjukan. Sisi akting memperlihatkan bahwa para aktor tidak hanya memainkan peransebagai tokoh tetapi juga sebagai dirinya sendiri melalui improvisasi. Hal ini menunjukkan bahwa lakon,pemanggungan, dan akting memenuhi ciri teatrikalisme sekaligus bertolak belakang dengan realisme.